Sex, hormones, and genotype interact to influence psychiatric disease, treatment, and behavioral research. Issue 1 (7th November 2016) - Gobinath, Aarthi R.; Choleris, Elena; Galea, Liisa A.M.
Abstract : Sex differences exist in the vulnerability, incidence, manifestation, and treatment of numerous neurological and psychiatric diseases. Despite this observation prominent in the literature, little consideration has been given to possible sex differences in outcome in both preclinical and clinical research. This Mini‐Review highlights evidence supporting why studying sex differences matter for advances in brain health as well as improving treatment for neurological and psychiatric disease. Additionally, we discuss some statistical and methodological considerations in evaluating sex differences as well as how differences in the physiology of the sexes can contribute to sex difference in disease incidence and manifestation. Furthermore, we review literature demonstrating that the reproductive experience in the female can render the female brain differentially vulnerable to disease across age. Finally, we discuss how genes interact with sex to influence disease risk and treatment and argue that sex must be considered in precision medicine. Together the evidence reviewed here supports the inclusion of males and females at all levels of neuroscience research. © 2016 Wiley Periodicals, Inc.